Ballet conditioning [videorecording (DVD)] - Gulan, Elise (Starz Home Entertainment, 2007)
One of the greatest secrets to a dancer's body is ballet conditioning, which focuses on all muscle groups. In this unique program, your muscles will work smoothly in unison to create a long, streamlined silhouette with flat abs.